Pengaruh Permainan Edukatif Berbasis Wordwall Terhadap Kemampuan Literasi Anak Usia 5-6 Tahun - Augina, Nurfaika; Rusmayadi; Asti, A. Sri Wahyuni; Dzulfadhilah, Fitriani (Journal of Early Childhood Education (JECE), 2025)
The purpose of this study was to investigate how Wordwall-based instructional activities affected the literacy abilities of Batara Bira Kindergarten students, ages five to six.  A nonequivalent control group design and a quasi-experimental methodology were employed in the quantitative study.  Thirty youngsters made up the study's sample, and they were split into two groups: fifteen in the experimental group and fifteen in the control group.  Tests, documentation, and observation were the methods utilized to gather the data. Word meaning, reading comprehension, and letter symbol recognition were used as measures of literacy skills. Descriptive statistical analysis and non-parametric statistical analysis with the Wilcoxon Sign Rank Test are two methods of data analysis used.  According to the data analysis results, Asym (2-tailed) = 0.001 <0.05 indicates that H_1 is accepted and H_0 is rejected. This indicates that the experimental class's literacy skills are superior to those of the control group, demonstrating the significant influence of Wordwall-based educational games on the literacy abilities of children between the ages of 5 and 6.